Association of Higher MERS-CoV Virus Load with Severe Disease and Death, Saudi Arabia, 2014 - Feikin, Daniel R.; Alraddadi, Basem; Qutub, Mohammed; Shabouni, Omaima; Curns, Aaron; Oboho, Ikwo K.; Tomczyk, Sara M.; Wolff, Bernard; Watson, John T.; Madani, Tariq A. (Emerging infectious diseases, 2015)
Middle East respiratory syndrome coronavirus (MERS-CoV) causes a spectrum of illness. We evaluated whether cycle threshold (Ct) values (which are inversely related to virus load) were associated with clinical severity in patients from Saudi Arabia whose nasopharyngeal specimens tested positive for this virus by real-time reverse transcription PCR. Among 102 patients, median Ct of 31.0 for the upstream of the E gene target for 41 (40%) patients who died was significantly lower than the median of 33.0 for 61 survivors (p=0.0087). In multivariable regression analyses, risk factors for death were age>60 years), underlying illness, and decreasing Ct for each 1-point decrease in Ct). Results were similar for a composite severe outcome (death and/or intensive care unit admission). More data are needed to determine whether modulation of virus load by therapeutic agents affects clinical outcomes.